Design and Analysis of a Novel Planar Translational Parallel Robotic Mechanism with Three Limbs. (October 2019) - Chen, Z H; Zhang, Y B; Wang, K M
Abstract: A novel planar translational parallel robotic mechanism with three limbs is designed. The degree of freedom (DOF) and output characteristics of mechanism are studied based on the screw theory. The mathematic models including position, velocity and acceleration are derived according to different forms of the actuated inputs. When the linear displacements of two cylindrical joints are selected as the actuated inputs, the velocity Jacobian is an identity matrix and the mechanism has fully isotropic kinematics characteristics. Singularity of the mechanism is discussed and all singular configurations are explored. Finally, kinematics simulation of the mechanism is carried out by ADMAS and MATLAB software, and the kinematic curves are drawn.